P2-S6.11 The cost-effectiveness of screening men who have sex with men for rectal chlamydial and gonococcal infection to prevent HIV infection. (10th July 2011) - Gift, T; Bernstein, K; Chesson, H; Marcus, J; Pipkin, S; Kent, C
Abstract : Background: Men who have sex with men (MSM) who have a current or recent history of rectal gonococcal (GC) or chlamydial (CT) infection are at greater risk for HIV than men with no history of rectal infection. This increased risk may be due to biological or behavioural factors. Screening and treating MSM for rectal CT/GC infection may help reduce any increased biological susceptibility to HIV infection and identify men at increased risk of HIV infection. Methods: We used a Markov state-transition model to examine the potential impact of screening MSM for rectal CT/GC infection. Observational data from San Francisco were used to estimate the incidence of rectal CT/GC in MSM, including repeat infection, and the HIV incidence in MSM with and without current or recent rectal CT/GC infection. Men were categorised into four risk strata based on the number of rectal infections they had experienced. We assumed the increased risk of HIV infection was due to a combination of factors: biological (relevant only when a given person had an untreated rectal CT/GC infection) and behavioural (relevant for a period of time after a rectal CT/GC infection was treated or resolved without treatment). The quality-adjusted life year (QALY) reduction due to HIV infection, the direct costs for testing and treatment for CT/GC, and the direct lifetime medical costs per case of HIV were drawn from the literature. In sensitivity analyses we varied assumptions about the duration of rectal CT/GC infection, biological vs behavioural attribution of the increased risk of HIV infection in those with rectal CT/GC, and incidence of repeat rectal CT/GC infection. We assumed a fixed proportion of MSM (both HIV-infected and HIV-uninfected) would be screened annually. HIV prevention was the only benefit of screening that we assessed; we did not include other health and economic benefits of treating rectal CT/GC. Results: In many scenarios, screening MSM for rectal CT/GC infection was cost-saving in that the discounted cost of screening and treatment was less than the discounted cost of averted HIV infections see Abstract P2-S6.11 Table 1 . The cost per QALY gained through rectal CT/GC screening ranged from < $0 to $50 000 in almost all scenarios examined, except when the elevated HIV risk in MSM with rectal infection was mostly attributed to behavioural factors rather than biological. Conclusions: Preliminary results suggest that screening MSM for rectal CT/GC infection can be a cost-effective intervention to reduce HIV infection.